'The Memory of the Tree': A New Theatrical Model of Genogram. Issue 2 (November 2017) - Fiaschini, Fabrizio
In the context of systemic psychotherapy, the genogram represents a model of graphical representation which the persons involved produce and comment on in order to provide information about their family of origin, from at least a three-generational perspective. This paper proposes a new variant of the genogram, focused on theatrical language: the result of a five-year experiment in the training of dramatherapists, psychologists, psychotherapists and counsellors. Starting from Stanislavski's and Grotowski's research, the paper highlights the potentialities that the theatre perspective may have with the genogram. Thanks to the 'emotive memory' and 'body-memory', the theatre can enrich the genogram method with a set of operational tools that can increase the introspective potential of the genogram itself, especially through the aid of physical actions. If the act of drawing represents an expressive 'medium' in the traditional genogram for stimulating the affective memory of family ties, then the language of performance can even better represent this medium, centred as it is on the activation of the body as a vehicle capable of bringing into contact the individual with his identity and his deep memory, even regarding the family, in order to creatively translate this into a communicative and narrative form.